2022
DOI: 10.1126/scitranslmed.abn7336
|View full text |Cite
|
Sign up to set email alerts
|

BLIMP1 and NR4A3 transcription factors reciprocally regulate antitumor CAR T cell stemness and exhaustion

Abstract: Chimeric antigen receptor (CAR) T cells have not induced meaningful clinical responses in solid tumors. Loss of T cell stemness, poor expansion capacity, and exhaustion during prolonged tumor antigen exposure are major causes of CAR T cell therapeutic resistance. Single-cell RNA-sequencing analysis of CAR T cells from a first-in-human trial in metastatic prostate cancer identified two independently validated cell states associated with antitumor potency or lack of efficacy. Low expression of PRDM1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 56 publications
0
28
0
Order By: Relevance
“…For example, NR4A and Tox family transcription factors were identified as key mediators of T cell exhaustion’s epigenetic and transcriptional programs ( 31 , 32 ). The hypoxic microenvironment leads to cellular mitochondrial dysfunction, triggering the expression of transcriptional repressor BLIMP1 and producing Tex ( 33 ). Several approaches to partially reverse the T cell exhaustion phenotype through gene editing or small molecules and enhance the efficacy of immunotherapy have also been found.…”
Section: Discussionmentioning
confidence: 99%
“…For example, NR4A and Tox family transcription factors were identified as key mediators of T cell exhaustion’s epigenetic and transcriptional programs ( 31 , 32 ). The hypoxic microenvironment leads to cellular mitochondrial dysfunction, triggering the expression of transcriptional repressor BLIMP1 and producing Tex ( 33 ). Several approaches to partially reverse the T cell exhaustion phenotype through gene editing or small molecules and enhance the efficacy of immunotherapy have also been found.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, another group recently reported that the deletion of the three NR4A family members was required to enhance the action of chimeric-antigen receptor (CAR) expressing CD8 + T cells 8 . Furthermore, a recent study showed that NR4A3 deletion in human CAR-T cells was not sufficient to enhance tumor control but that the co-deletion of Nr4a3 and Prdm1 (coding for Blimp-1) is required to decrease exhaustion and improve tumor control 11 . One possible explanation for these differences could relate to the stronger antigenic signal that may lead to more severe exhaustion of CAR-expressing TILs, which might not be overcome by the deletion of only one NR4A member in CD8 + TILs.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, NR4A3 deficiency in CD8 + T cells favors the generation of memory precursor effector cells and central memory CD8 + T cells while at the same time enhancing effector functions 7 . Several studies have shown that NR4As also influence CD8 + T cell responses during chronic responses [8][9][10][11] . It was reported that the deletion of the three members of the NR4A family (TKO) enhances the anti-tumor response of CAR-T cells used for adoptive cell therapy (ACT) of tumor-bearing mice 8 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, exhausted T cells experience metabolic changes such as impaired glycolysis 13 . Transcriptional and epigenetic changes include alterations in the activity of several transcription factors including: TCF-7, TOX, T-BET, EOMES, PRDM1, NR4A3, BATF, EGR2, and AP-1 and RUNX family members [14][15][16][17][18][19][20][21][22][23][24][25][26] . In an effort to control the epigenetic response to chronic stimulation, several studies have used genetic engineering tools to overexpress or knockout individual molecules.…”
Section: Introductionmentioning
confidence: 99%